Analisis Strategi SD Negeri 2 Cibunigeulis Kota Tasikmalaya dalam Meningkatkan Mutu Pendidikan di Era Disruptif - Tyas Chandra Puspita; Giska Nur Azkiya; Ichsan Fauzi Rachman (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study aims to determine the strategies applied by State Elementary School 2 Cibunigeulis in improving the quality and quality of education in the midst of rapid technological changes and developments. This research is a type of descriptive research that uses a qualitative approach. The research data obtained by researchers are data from observations and interviews with the principal and teachers of SD Negeri 2 Cibunigeulis. Based on the results of the research, information was obtained that cooperation with various parties, utilizing technology, forming a bullying task force, making special coaching efforts, and improve academic and non-academic achievements are strategies used by SD Negeri 2 Cibunigeulis to improve the quality and quality of education in the midst of a disruptive era. Overall, the research confirms that SD Negeri 2 Cibunigeulis is able to adapt well to the disruptive era by creating a modern educational environment and improving the quality of educators on an ongoing basis